Impaired Skeletal Muscle Regeneration Induced by Macrophage Depletion Could Be Partly Ameliorated by MGF Injection - Liu, Xiaoguang; Zeng, Zhigang; Zhao, Linlin; Chen, Peijie; Xiao, Weihua (Frontiers in Physiology, 2019)
Skeletal muscle injury is one of the most common injuries in sport medicine. Our previous study found that macrophage depletion impaired muscle regeneration and that mechano growth factor (MGF) may play an important role in this process. However, whether injection of MGF protects against impaired muscle regeneration after macrophage depletion has not been explored. Therefore, we generated a muscle contusion and macrophage depletion mouse model and injected MGF into the damaged muscle. Comprehensive morphological and genetic analyses were performed in the injured skeletal muscle after macrophage depletion and MGF injection. The results showed that injection of MGF did not exert a protective effect on muscle fiber regeneration but decreased fibrosis in the contused skeletal muscle after macrophage depletion. Moreover, MGF injection decreased the expression of muscle inflammatory cytokines (TNF-α, IFN-γ, IL-1β and TGF-β), chemokines (CCL2, CCL5 and CXCR4), oxidative stress factors (gp91phox) and matrix metalloproteinases (MMP-1, MMP-2, MMP-9, MMP-10 and MMP-14). These results suggest that the impairment of skeletal muscle regeneration induced by macrophage depletion could be partly ameliorated by MGF injection and that inflammatory cytokines, oxidative stress factors, chemokines and matrix metalloproteinases may be involved in the process.